Sosiologi Pendidikan Michel Foucault: Kritik dan Dialog antara Ideologis dengan Praksis Pendidikan - Almas, Afiq Fikri (Nusantara: Jurnal Pendidikan Indonesia, 2024)
Purpose – This research aims to discuss Michel Foucault's sociology concept of education theory and criticize the dialogue between ideology and educational practice based on several of Foucault's works. This is because Foucault rejects the concept of power that is negative. And he proposed the concept of power-knowledge which underlines that there is no power without knowledge, and vice versa. Foucault also observed the shift from monarchical power to disciplinary power in modern society, which is reflected in educational practices and needs to be addressed.Method – The research methodology approach was conducted through a literature review of Foucault's works and relevant sociological theories.Findings – The research results explain that Foucault emphasizes the importance of the relationship between power, knowledge, discipline, and punishment in the context of education. In the context of education, the practice of power is reflected in standardization, selection, and punishment systems. Foucault criticizes standardization and selection practices that can create social inequality and identifies more internalized forms of punishment such as educational punishment. However, he proposed a critique of the use of power and control in education that ignores aspects of students' individuality and critical consciousness. Research Implications – Thus, this research can provide benefits to academics and educational practitioners to understand and apply Foucault's concepts in the context of education. It is useful to encourage critical and reflective thinking towards existing educational practices and explore new ways to achieve more inclusive and humanizing educational goals. Foucault also introduced the concept of the Panopticon that can be applied in education, where schools will become efficient places of surveillance for teachers against students.